An An Evaluation of Competency in Rational Drug Use of Nursing Graduates - Charoensuk, Sukjai; Leungratanamart, Ladda; Reunreang, Tutiyarat; Turner, Kamolrat; Theinpichet, Suntharawadee (Journal of The Royal Thai Army Nurses, 2020)
This descriptive study aimed to examine perceived competency in rational drug use of nursing graduates in bachelor of nursing science program after an implementation of integrating the rational drug use curriculum into the bachelor of nursing science program in academic year B.E. 2561. The population included 9,249 newly nurse graduates from 86 nursing education institutes in academic year B.E. 2561, and 4,269 graduates (46.15%) responded. The instrument used was a 46-item questionnaire regarding competency in rational drug use developed by the researchers based on the Prescribing Competency Framework, composed of 2 main competencies which were consultation and prescribing competencies. Data collecting was done online. Data were analyzed using descriptive statistics. The results revealed that nursing graduates perceived their overall competency in rational drug use was at a high level ( = 4.31, SD = 0.48). All categories of the competency were also rated at a high level. The highest score fell in the category of working with others as inter-professional team to promote rational drug use ( = 4.39, SD = 0.57). The lowest score was found in the category of considering the options ( = 4.22, SD = 0.53). Considering items in each category, the highest score was found in “assess the patient’s history” ( = 4.51, SD = 0.60). The study suggested that the Thailand Nursing and Midwifery Council should promote all nursing education institutes to integrate the rational drug use curriculum into their nursing curriculum in order to improve nursing competencies continuously.